Short-term effect of oil supplementation of complementary food on total ad libitum consumption in 6- to 10-month-old breastfed Indian infants - Bajaj, M; Dubey, A P; Nagpal, J; Singh, P K; Sachdev, H P S (Journal of pediatric gastroenterology and nutrition, 2005)
To evaluate the short term effect of oil supplementation of complementary food on total ad libitum consumption in breastfed infants. Twenty infants between 6 to 10 months of age were studied in a tertiary hospital in New Delhi for 48 hours. They were given three semi-solid complementary feeds per day and ad libitum breastfeeding. No other food or fluid was allowed during the study period. A traditional gruel made of rice and pulses with high energy density (oil added; caloric density = 35 kcal/100 g) or low energy density (without oil; caloric density = 20 kcal/100 g) was offered in a randomized manner on consecutive days to all infants. Total caloric intake from breast milk and semi-solids was computed for each day. Infants consumed an equivalent amount of semi-solid (mean difference, 10.75 g/day; 95% confidence interval, 10.56 to 32.06; P = 0.304) and a lower amount of breast milk (mean difference, 121.1 g/day; 95% confidence interval, 35.13 to 207.16; P = 0.008) when high energy density feeds were offered. Although the caloric intake from semi-solids increased significantly (18.9 kcal/day; 95% confidence interval, 12.9 to 24.8; P < 0.001) with the high density diet, the total caloric intake (breast milk and study feeds) decreased (mean difference = 59.6 kcal/day; 95% confidence interval, 5.95 to 113.34; P = 0.031). An inverse relationship was found between caloric density of semi-solids and breast milk intake (r = 0.34, r = 0.12, P = 0.032). In the short term, oil supplementation of complementary food in breastfed infants does not translate into enhanced total caloric intake, primarily as a result of breast milk displacement.